1999
DOI: 10.1164/ajrccm.159.2.9803121
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo-controlled Crossover Trial of Continuous Positive Airway Pressure for Mild Sleep Apnea/Hypopnea Syndrome

Abstract: The minimal disease severity at which patients with the sleep apnea/hypopnea syndrome (SAHS) gain benefit from treatment is not well characterized, although a pilot study of continuous positive airway pressure (CPAP) therapy showed daytime improvements in patients with 5 to 15 apneas + hypopneas per hour slept (AHI). We have thus performed a second, larger, randomized, placebo- controlled study in a prospective series of 34 patients (13 female) with mild SAHS (AHI 5 to 15) and daytime sleepiness. Patients spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
342
2
15

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(384 citation statements)
references
References 30 publications
25
342
2
15
Order By: Relevance
“…In this study patients were followed for 4 weeks. The results remarkably resembled those in the studies by ENGLEMAN et al [12,13,19], showing that the measures of subjective well-being improved about two-fold compared with placebo. Therefore, from the short-term studies available it can be deduced that placebo or subtherapeutic CPAP have measurable positive effects on subjective well-being, but that there is a clear quantitative difference between CPAP and placebo effects.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study patients were followed for 4 weeks. The results remarkably resembled those in the studies by ENGLEMAN et al [12,13,19], showing that the measures of subjective well-being improved about two-fold compared with placebo. Therefore, from the short-term studies available it can be deduced that placebo or subtherapeutic CPAP have measurable positive effects on subjective well-being, but that there is a clear quantitative difference between CPAP and placebo effects.…”
Section: Discussionsupporting
confidence: 83%
“…In a smaller group of patients, a similar benefit of CPAP over placebo was reported by the same group [13]. In a further study, this group showed that CPAP therapy also significantly improved well-being in patients with mild sleep apnoea/hypopnoea syndrome as assessed by the Epworth sleepiness scale, a symptom score, performances on two of seven cognitive tasks, depression score, and five subscales of the Short Form-36 health/functional status questionnaire [19].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This study not only suggests that older individuals with OSA benefit from CPAP treatment, but those with the additional burden of Alzheimer's disease can utilize this therapy achieving gains in alertness. (19,20,22,44) failed to show improvement in objective sleepiness with CPAP treatment, compared to those with more severe disease. (21,23,30,32) CPAP appears to be beneficial in improving self-reported daytime sleepiness in older adults and even in those with dementia, but evidence does not show that it is superior to conservative therapy or placebo for increasing objectively measured daytime sleepiness.…”
Section: Daytime Sleepinessmentioning
confidence: 98%
“…"Cut-off points" describing certain hours of nightly CPAP use have been described by other investigators. Some of these "cut-off points" have been set at arbitrary levels [2], based on median group values [3], or based on outcome data related to sleepiness and performance [4]. It has also been suggested that compliance is better defined by CPAP use in relation to total subjective sleep-time.…”
mentioning
confidence: 99%